2020
DOI: 10.1017/s0003055420000192
|View full text |Cite
|
Sign up to set email alerts
|

Roll-Call Vote Selection: Implications for the Study of Legislative Politics

Abstract: Roll-call votes provide scholars with the opportunity to measure many quantities of interest. However, the usefulness of the roll-call sample depends on the population it is intended to represent. After laying out why understanding the sample properties of the roll-call record is important, we catalogue voting procedures for 145 legislative chambers, finding that roll calls are typically discretionary. We then consider two arguments for discounting the potential problem: (a) roll calls are ubiquitous, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our analysis is restricted to roll‐call votes which constitute about 5% of all votes taken in the German parliament (Sieberer et al 2020). Although there are reasonable doubts regarding their representativeness (Ainsley et al 2020), they often cover controversial (Crisp and Driscoll 2012) and, thus, politically relevant decisions. For Germany, roll calls represent the only source of individual‐level voting behavior in parliament.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis is restricted to roll‐call votes which constitute about 5% of all votes taken in the German parliament (Sieberer et al 2020). Although there are reasonable doubts regarding their representativeness (Ainsley et al 2020), they often cover controversial (Crisp and Driscoll 2012) and, thus, politically relevant decisions. For Germany, roll calls represent the only source of individual‐level voting behavior in parliament.…”
Section: Methodsmentioning
confidence: 99%
“…While scholars and commentators agree that ideological polarization in the US Congress emerged in the late 1970s or early 1980s, the root causes of this polarization are still being investigated. Polarization in Congress can be measured by analyzing the roll-call votes of each lawmaker over time [13][14][15]. Approximately four decades ago, the most conservative Democratic congressperson was more ideologically conservative than the most liberal Republican [9,12,14,16,17].…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Second, we proceeded to estimate parties’ positions from roll-call data. Nominal votes are exceptional in Latin American politics, and Uruguay is not the exception (Carey 2009; Zucco 2013; Ainsley et al 2020). Because the dataset allows for a specific search of words and text patterns, we searched for all the available roll calls during the period.…”
Section: Estimating Policy Positions Of Uruguayan Parties Using Roll-...mentioning
confidence: 99%
“…Because the dataset allows for a specific search of words and text patterns, we searched for all the available roll calls during the period. In line with Ainsley et al (2020), we identified roll-call votes from an automatized search for regular expressions. 5 However, unlike Ainsley et al (2020) or Zucco (2013), we decided to keep only the roll calls associated with the treatment of executive vetoes that take place in the Asamblea General, since the vast majority of nominal votes in the lower or upper chambers refer to specific issues on administrative decisions of the chamber (e.g., the election of authorities and other administrative personnel) that cannot be coerced into yes or no, which is crucial to running the W-nominates algorithm.…”
Section: Estimating Policy Positions Of Uruguayan Parties Using Roll-...mentioning
confidence: 99%